Readings in industrial organization and public policy: selected by a Committee of The American Economic Association - Heflebower, Richard Brooks; American Economic Association (Homewood, Ill., Published for the association by R. D. Irwin, 1958)
This book aims to provide for nonspecialists a convenient compilation of the more important articles in the field of industrial organization and public policy. it is also a book of readings useful in teaching graduate courses in this field.
Includes bibliography.
oo 22/10/2018
Loans
Keywords: Industries; Industrial management